2022
DOI: 10.3390/jcm11206027
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thyroid Disorders Are More Prevalent in Patients with Celiac Disease: A Retrospective Case-Control Study

Abstract: Background. Among patients with celiac disease (CD), there is an increased incidence of autoimmune thyroid disorders (AITDs), with hypothyroidism being more frequent than hyperthyroidism. This retrospective case-control study aimed to explore the prevalence of TDs in a population of adult celiac patients from Northern Sardinia, a geographic area with a high prevalence of autoimmune disorders. Methods. Data were collected from consecutive patients with CD (cases) and without CD (controls) who were undergoing up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Similarly, current and former smokers were more represented among cases than among controls. Interestingly, the frequency of CD patients was only 2.2% among those with a diagnosis of CVD, while it was 9.5% among controls, i.e., a value consistent with previous results observed in the same population [ 8 ]. The prevalence of dyslipidemia was threefold higher in patients with CVD compared with patients without CVD (20.1% vs. 6.8%) ( Table 1 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, current and former smokers were more represented among cases than among controls. Interestingly, the frequency of CD patients was only 2.2% among those with a diagnosis of CVD, while it was 9.5% among controls, i.e., a value consistent with previous results observed in the same population [ 8 ]. The prevalence of dyslipidemia was threefold higher in patients with CVD compared with patients without CVD (20.1% vs. 6.8%) ( Table 1 ).…”
Section: Resultssupporting
confidence: 91%
“…It is widely known that CD can be associated with multiple organ involvement, which justifies its classification as a systemic disorder [ 5 ]. Aside from its association with other autoimmune diseases such as type 1 diabetes, Hashimoto’s thyroiditis, and primary sclerosing cholangitis [ 8 , 14 , 43 ], usually explained by the sharing of various immune mechanisms [ 44 ], the potential association between CD and CVD has gained a lot of interest during the past decade, and the literature is currently recording an exponential growth of publications on this specific field. Most studies in this area, whether observational studies [ 45 ], prospective studies [ 20 , 46 ], or meta-analyses [ 23 , 24 , 25 ] have reported an increased atherogenic cardiovascular risk in CD patients, especially related to coronary or peripheral districts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of gluten from a diet is a treatment for diseases such as celiac disease, Duhring’s disease, wheat allergy, or non-celiac gluten sensitivity (NCGS) [ 43 ]. Among patients with Hashimoto’s disease, celiac disease is more prevalent [ 44 ]. This may result in a higher levothyroxine requirement owing to the lower absorption capacity of LT4 in the gastrointestinal tract [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the frequency of developing this disease increases with the age of patients (especially after 60 years of age); however, more and more often, this entity is also diagnosed in young people and even children [ 6 , 7 , 8 , 9 ]. The causes of hypothyroidism and thus the development of HD are many, ranging from genetic factors and hormonal changes to environmental factors, as well as the presence of other comorbidities, especially those of autoimmune origin [ 10 , 11 , 12 , 13 ]. HD itself is classified as a subunit of autoimmune diseases, which means that its development is closely related to the deregulation of the immune system, and, more specifically, to the development of inflammation caused by the host’s immune cells (in particular T lymphocyte-induced apoptosis of thyroid follicular cells) that attack the thyroid [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%